Os territórios dos Maracatus do povoado Brejão - Brejo Grande/SE - Oliveira, Edivaldo Alves de (2017)
This work had the purpose of analyzing, in the context of Cultural Geography, the territories of the Maracatus that manifest themselves in Brejão village, belonging to the municipality of Brejo Grande and located near the mouth of the São Francisco River in Sergipe. As cultural and symbolic manifestations we tried to analyze which elements contribute to the construction and formation of merrymakings in the village. For comprehension and analysis of the popular manifestations under study, the categories space and territory were adopted for the apprehension of territorialities and, methodologically, the qualitative approach, developed by a set of procedures: documentary research in academic texts, reports, websites and censuses; interviews with the Maracatu players and with the population; workshop with students from 10 to 29 years old of the village State School, and participant research with the Maracatu Nação Puerto Rico (MNPR) in Recife city before and after the carnival of 2016. To understand the origins of the Maracatus, we used historical texts on the African Diaspora and the work, religious and festive daily life of Africans, in order to understand the syncretism between the candomblé and the catholic religion, but especially today, the links between catholic festivities and the manifestation of Maracatu groups. The realization of the workshop made possible the identification of the cultural expressions existing in the village, among them, those that give identity support, emphasizing the Maracatu as one of the place references. From the interviews with the players, it can be seen that the Maracatus of Brejão manifest themselves in the moments of 'time off'; they have the same family origin and play with the formation of relatives and aggregates. The history of Maracatu as a popular manifestation of blacks is confused with the history of the village that, although formed in the XIX century, is inserted in a region which since the XVIII century has recorded the formation of quilombos. Through orality, until 2006 there was only the Maracatu Patrocínio do Brejão (MPB) in the village, originated from Mestre Plácido formation and led by his niece Mestre Lila since 1940. With the insertion of Brejão village in the Quilombola Brejão dos Negros, created by the Federal government, there was a schism in the merrymaking and Mestre Adalto, a MPB player creates the Maracatu Raízes do Quilombo (MRQ), distinguishing, in origin, as a formation that supports the movement to incorporate the village as a quilombo. Both are manifested as the MNPR because they are already disassociated from the popular processions of the Christmas cycle, for keeping elements of the court and the drums in the sense of joke, but they are distinct because they do not associate the formation with candomblé rituals. It was observed singular elements in the sense of play, in the formation of the territories and in the practices of the studied Maracatus, both, cultural reference of the village, being it Brejão or Brejão dos Negros.